Blind adaptive reduced-rank detection for DS-CDMA signals in multipath channels. - Yu Song (IEEE Journal on selected areas in communications)
Blind adaptive multiuser detection for direct sequence code division multiple access (DS-CDMA) signals over static and time-varying intersymbol interference (ISI) limited channels is considered. Blind adaptive detectors must be robustified for ISI channels, when there is significant mismatch between the received signature vector and the transmitted code (assumed known at the receiver). A new low-complexity detector is presented that improves on some previously proposed methods without explicit estimation of the ISI channel. The key innovation is a reduced-rank detector architecture combined with an efficient subspace tracker that yields direct accurate estimation of the desired user's received signature. Several representative simulation examples of detector output signal-to-noise-and-interference ratio (SINR) for fading channels are provided in support of our claims of improved efficacy of the method